Enabling Key Technologies and Emerging Research Challenges Ahead of 5G Networks: An Extensive Survey - C. Amali; B. Ramachandran (JOIV : International Journal on Informatics Visualization, 2018)
The evolution towards 5G networks is expected to slake the growing thirst of internet traffic with improved Quality of Service (QoS) and reduced energy consumption and cost. The increased penetration of smart devices and induction of arising multimedia applications, together with high quality video services are already crafting a milestone on existing cellular networks. These surging demands dictate that radical enhancements need to be made in cellular architecture to drift towards ultra-dense networks. The 5G system is envisioned to achieve improved data rate, increased capacity, decreased latency, and enhanced spectral efficiency in order to provide technical solution for the challenges behind the cellular networks. Thus, the 5G era is emerging to quench the increasing demand for network capacity, to manage explosive growth of traffic patterns and to face the challenges caused by the proliferation of versatile applications and high-end devices. In this paper, we make a broad survey on 5G cellular network architecture and some of the promising key technologies such as cloud RAN (Radio Access Network), Software-Defined Networking (SDN), Network Function Virtualization (NFV) and modulation formats. Finally, this ground-breaking survey highlights major existing research issues and possible future research directions in the next new era of mobile wireless networks.